Impact of different farming scenarios on key soil sustainability indicators driving soil carbon and system productivity of rice-based cropping systems - Mishra, Ajay Kumar; Maurya, Piyush Kumar; Sharma, Sheetal (Frontiers in Plant Science, 2024)
This research explores the relationships among soil characteristics, carbon dynamics, and soil biome in rice-based cropping systems across four farming scenarios: conventional farming, organic farming with conventional tillage, integrated nutrient management, and conservation agriculture with zero tillage. Conducted at the International Rice Research Institute, India (2020-2022), the study analyzed physical, chemical, and biological soil parameters. The findings reveal significant effects of farming scenarios on soil organic carbon (SOC), available nitrogen (N), phosphorus (P), and potassium (K), with no notable impact on bulk density, pH, electrical conductivity, or water-holding capacity. Organic farming enhanced microbial health, showing microbial biomass carbon (MBC) at 194.0 μg g-1, microbial biomass nitrogen (MBN) at 134.2 μg g-1, and dehydrogenase activity (DHA) at 36.80 μg TPF h-1 g-1, reflecting a more active microbial community important for nutrient cycling. Conservation agriculture reduced soil compaction, promoting better root growth and water penetration, leading to higher crop yields (10.95 ± 0.49 t ha-1). The study highlights the role of SOC in enhancing soil health, nutrient availability, and crop productivity, emphasizing sustainable agricultural practices.